Determination of Minimum Inhibitory Concentration of Different Antibiotics against Pseudomonas aeruginosa by E- test at a Tertiary Care Hospital - Khatun, Mst Romena; Alam, Kh Md Faisal; Nahar, Sabera Gul; Begum, Nurjahan; Shahrear, Md Khaled; Hauqe, Quazi Tamanna (TAJ: Journal of Teachers Association, 2023)
Background: Antimicrobial drug resistance is a matter of worldwide concern. Different microorganisms, including bacteria, are becoming more resistant day by day. So it is of utmost importance to know the antimicrobial susceptibility pattern not only for initiation of treatment but also for prevention of drug resistance. By determining minimum inhibitory concentration (MIC) by Epsilometer-test (E-test), we can determine the exact dose of a particular drug. Aims: The study is aimed to determine the MIC of different antibiotics against intermediate isolates of P. aeruginosa isolated from clinically suspected patients of chronic suppurative otitis media (CSOM). Materials and Methods: A cross-sectional type of descriptive study was conducted in the Department of Microbiology, Rajshahi Medical College, Rajshahi, during the period of January 2019 to December 2019 to identify the causative bacteria of CSOM with their antibiotic susceptibility pattern. A total of 96 aural swabs were collected from clinically suspected cases of CSOM, irrespective of age and sex, in the ENT department of Rajshahi Medical College Hospital, Rajshahi. Isolation and identification of bacteria were made as per standard procedure, and then antimicrobial susceptibility testing was performed by the disc diffusion method. At last, E-test was performed on different antibiotics against intermediate isolates of P. aeruginosa. Results: Among 73 isolates, 37 showed intermediate susceptibility towards selected antibiotics such as beta-lactams (Ceftazidime, Ceftriaxone), aminoglycosides (Gentamicin), and quinolones (Ciprofloxacin) by disc diffusion method. Among 37 intermediate isolates, P. aeruginosa was 14 in number. Regarding MIC breakpoints in terms of susceptibility, out of 14 intermediate isolates of P. aeruginosa, 09(64.28%) isolates were susceptible, 03(21.43%) intermediate, and 2(14.28%) were resistant to different antibiotics by E-test. Conclusion: In this study, higher susceptibility of different antibiotics against intermediate isolates of P. aeruginosa was observed by E-test than the disc diffusion method. TAJ 2022; 36: No-1: 47-54